Unemployment in South Africa: The Nature of the Beast. - Kingdon, G; Knight, J (2004)
Unemployment in South Africa is so widespread that it demands an explanation. This paper examines a central question about South African unemployment. Why do the unemployed not enter the informal sector, as is common in other developing countries? The data do not support the idea that unemployment is largely voluntary. The policy implications--that government should diminish labor market segmentation and the obstacles to entering the productive informal sector--may be relevant also to other developing countries with high unemployment.